Angiogenesis of extra- and intraembryonic blood vessels is associated with expression of nestin in endothelial cells - Mokrý, J; Nemecek, S (Folia biologica, 1998)
For a long time, intermediate filament protein nestin was recognized as a specific constituent of the cytoskeleton of developing neural cells and skeletal muscle. Recent reports by other investigators demonstrated that nestin may also be expressed in other cell types. Here we give evidence that nestin is expressed by endothelial cells of developing blood vessels in the rat. Using anti-Rat-401 monoclonal antibody we identified high levels of nestin in the endothelium lining all blood vessels of E14-15 rat foetuses. Immunoreactivity for nestin was detected in both extraembryonic (chorion, placenta, umbilical cord) and intraembryonic blood vessels. In the body of the foetus, we observed nestin-positive endothelial cells in vessels located in the areas of the mesenchyme as well as in vessels supplying the developing organs (central nervous system, liver, lung, spleen, heart, digestive tube). The strongest positive signal was given by the endothelium of newly vascularized tissues. In contrast to the developing tissues, expression of nestin by vascular endothelial cells was greatly reduced in adult tissues.
Keywords: Intermediate Filament Proteins; Endothelium, Vascular; Nerve Tissue Proteins; Pregnancy; Blood Vessels; Rats; Gestational Age; Fetus; Immunohistochemistry; novorozená zvířata; gestační stáří; fyziologická neovaskularizace; cévy; proteiny intermediálních filament; potkani Wistar; nestin; Animals; Animals, Newborn; zvířata; cévní endotel; plod; Neovascularization, Physiologic; proteiny nervové tkáně; tkáňová distribuce; krysa rodu Rattus; Nestin; imunohistochemie; Rats, Wistar; ženské pohlaví; těhotenství; Female; Tissue Distribution